The Treatment Group and Recidivism: A Multilevel Analysis of Prison-Based Substance Abuse Treatment. (November 2019) - Kelly, Christopher E.; Welsh, Wayne N.; Stanley, Jennifer N.
This study contributes to the substance abuse treatment literature by examining recidivism across treatment groups, the level of aggregation between the individual and the program. The sample consisted of 618 drug-involved offenders who participated in 12 different treatment groups within a single prison. Reincarceration significantly varied across groups, controlling for time at risk and treatment modality. This between-unit variation was explained by individual level treatment response measures and control variables. Results demonstrated that treatment effectiveness is impacted by the group in which the individual participates. These findings have substantial implications for correctional treatment theory, research, and policy.